ELASTISITAS HARGA CABAI DAN PENDAPATAN PEDAGANG KAKI LIMA DI KOTA DENPASAR - Pratama, I Gede Risky; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 9, September 2018 (pp. 1826-2070), 2018)
The condition of rising prices of food raw materials, especially chili is bad for all people. The purpose this research is 1) to know the nature of the demand of chili as a result of chili price change among the street vendors in Denpasar City, 2) to know the influence of chili price increase on the amount demanded on pepper among street vendors in Denpasar, 3) the price of chili to the amount requested for tomatoes among street vendors in Denpasar City and 4) to determine the effect of chili price changes to the income of street vendors in Denpasar. The data used is primary data by distributing questionnaires to 60 street vendors. The analysis technique used Regression Simple Double Log. The test results show that 1) the nature of the demand for chili as a result of chili price changes among the street vendors in Denpasar City is inelastic. 2) Increasing the price of chili does not positively affect the amount demanded on pepper. 3) Increasing the price of chili has a negative effect on the amount requested on tomatoes. 4) Chili price has a negative effect on PKL's participation in Denpasar City.